Rheology of Aqueous Ferrofluids: Transition from a Gel-Like Character to a Liquid Character in High Magnetic Fields - Stanislav Čampelj (ChemEngineering, 2023)
Rheological measurements under an applied magnetic field were used to investigate the changes to the internal structure and stability of an aqueous ferrofluid. The ferrofluid was prepared by dispersing 1.8 wt.% of maghemite nanoparticles with a size of d = 14 ± 3 nm and a saturation magnetization MS = 68 emu/g in water using citric acid as the surfactant. In this study, oscillatory tests were used to investigate the internal structural changes and the stability of ferrofluid under the influence of the magnetic field B. In a magnetic field of approximately 50 mT, the G′ became higher than the loss modulus G″ as the ferrofluid exhibited a gel-like character. However, at a magnetic field of approximately 200 mT, the character of the ferrofluid reverted to that of a liquid. The change in the character of the ferrofluid in this high magnetic field was associated with a gradual change from chain agglomerates to the energetically more favourable globular agglomerates, using a calculation based on a model described in a separate work. The globular agglomerates impeded the flow to a much lesser degree than the chains, causing a reduction in the viscosity. Further increase of the magnetic field resulted in sedimentation of agglomerates and loss of magneto-rheological effect.